The Importance Of Moving Games In The Development Of Sports Motivation Of Boxers Engaged In The Initial Preparatory Stage 11-13 Years - J.M.Ergashev (Zien Journals, 2021)
In this article, the results of scientific research work on the determination of sports motivation of boxers engaged in the initial preparatory stage are described. Sports motivation V.F.Carried out on the case using the Sopov methodology.
Keywords: Boks; sports motivation; initial preparation; action games